Cross-sectional longitudinal study of the academic half-day format in a hematology-oncology fellowship training program - Eid, Ahmed (BMC Med Educ, 2015)
BACKGROUND: Few published studies have evaluated the effectiveness of changing the traditional curriculum of several hourly educational sessions per week to an academic half-day (AHD) educational format. This study describes our experience with implementing an AHD format in the Hematology-Oncology Fellowship Program at The University of Texas MD Anderson Cancer Center and evaluates the perceptions that learners had for this format. METHODS: Using a mixed quantitative and qualitative approach, we evaluated our AHD program using four yearly fellows’ surveys to assess the Hematology-Oncology Fellows’ perceptions of the effectiveness of the AHD format. We analyzed the fellows’ perceptions using descriptive statistics and thematic analysis of the qualitative data collected from the surveys. We used a quality improvement approach by implementing and testing changes to the AHD over 4 years on the basis of the data collected from the yearly fellows’ surveys. We also collected third-year fellows’ Oncology In Training Exam (ITE) scores from 2008 to 2014. RESULTS: We found that the fellows perceived the AHD format favorably; fellows agreed that they had more motivation to attend AHD, more concentration during the sessions, more effective weekly work organization, and increased knowledge retention. We established the reliability of our survey tool (Cronbach’s alpha = 0.83) as well as content and construct validity. We saw an increasing trend in ITE scores since the AHD was implemented. CONCLUSIONS: Our results contribute to further understanding the effect of the AHD format on trainees. Using a continuous evaluation and an educational quality improvement strategy, we found that the AHD curriculum was associated with a rising trend in learners’ exam scores and increased learner satisfaction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-015-0418-y) contains supplementary material, which is available to authorized users.